MAINSTREAMING RELIGIOUS MODERATION IN INDONESIA: READING AND UNDERSTANDING WASATIYAH IN THE QUR’AN - Fawaid, Ahmad (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2024)
Religious moderation in Indonesia emerged as a response to increasing intolerance, radicalism, and religious-based conflicts. Despite having a strong foundation, the implementation of this concept still faces challenges such as political and religious polarization, the spread of hoaxes, and the low level of public understanding of religious moderation. M. Quraish Shihab, as one of the contemporary tafsir figures, actively voices the importance of moderation through his writings, including the book “Wasathiyyah: Wawasan Islam tentang Moderasi Beragama”. This study aims to analyze the concept of religious moderation according to M. Quraish Shihab’s perspective, explain its relevance in the context of Indonesian society, identify challenges in its implementation, and provide strategic recommendations for strengthening religious moderation in society. This study uses a descriptive qualitative method with a library research approach. The analysis was carried out on primary and secondary sources, including books, journals, scientific articles, and relevant official documents. The analysis technique used is content analysis with a thematic approach. This study found that the concept of religious moderation put forward by M. Quraish Shihab emphasizes balance in belief, thought, and action. Moderation is defined as an effort to maintain a balance between various poles, such as the soul and body, religion and state, and reason and religious texts. This study provides theoretical contributions in enriching the study of religious moderation as well as practical contributions as references for the government, educational institutions, and society in realizing harmony in religious and state life.